BRAND IMAGE: TINJAUAN PUSTAKA SISTEMATIS HIBRIDA DAN ANALISIS BIBLIOMETRIK - Naia Salma Nabilah; Thayib Thayib (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Purpose - A growing number of studies have examined brand image over the past several decades; however, comprehensive, in-depth, and systematically structured research on this topic remains limited. Therefore, this study aims to conduct a systematic literature review combined with bibliometric analysis to examine brand image based on existing empirical evidence. Design/Methodology/Approach - This study adopts a Systematic Literature Review (SLR) approach by employing the keyword “brand image” in article titles, abstracts, and keywords within the Scopus database. The search process identified 16.700 publications published between 1983 and 2025. Data collection was carried out on January 31, 2025, and the retrieved publications were subsequently analyzed using bibliometric techniques supported by VOSviewer software. Findings - Based on the literature review, a total of 6.712 articles were identified from various academic publication sources. Research activity on this topic has shown significant intensity since 1976, marked by an increasing number of scholarly works produced by researchers. Most of these articles are written in English and published in reputable academic journals. In terms of country contributions, the United States ranks first as the leading contributor of publications. The disciplines most frequently covering these studies include business, management and accounting, social sciences, as well as economics, econometrics, and finance. Research Limitations/Implications - This study relies exclusively on articles indexed in the Scopus database, which may limit the generalizability of the findings. Future studies are encouraged to incorporate additional academic databases, such as the Web of Science, to broaden the scope and enhance the robustness of research outcomes. In practice, brand image serves as the foundation for an effective promotional strategy by creating a consistent brand image that aligns with the celebrity image, brand values, and consumer preferences. This alignment creates positive perceptions and consumer trust, thereby increasing marketing effectiveness and purchasing decisions. Social Implications - This study offers analytical insights for academics, practitioners, and the wider community regarding the sustainable application of celebrity endorsement principles derived from the Qur’an and Hadith. Originality/Value - Although research on brand image continues to expand globally, comprehensive and integrative studies remain scarce. Accordingly, this study contributes by systematically mapping the intellectual development and future research directions of brand image